Production and Characterization of Monoclonal Antibodies against Human Nuclear Protein FAM76B - Zheng, Xiaojing (PLoS One, 2016)
Human FAM76B (hFAM76B) is a 39 kDa protein that contains homopolymeric histidine tracts, a targeting signal for nuclear speckles. FAM76B is highly conserved among different species, suggesting that it may play an important physiological role in normal cellular functions. However, a lack of appropriate tools has hampered study of this potentially important protein. To facilitate research into the biological function(s) of FAM76B, murine monoclonal antibodies (MAbs) against hFAM76B were generated by using purified, prokaryotically expressed hFAM76B protein. Six strains of MAbs specific for hFAM76B were obtained and characterized. The specificity of MAbs was validated by using FAM76B(-/-) HEK 293 cell line. Double immunofluorescence followed by laser confocal microscopy confirmed the nuclear speckle localization of hFAM76B, and the specific domains recognized by different MAbs were further elucidated by Western blot. Due to the high conservation of protein sequences between mouse and human FAM76B, MAbs against hFAM76B were shown to react with mouse FAM76B (mFAM76B) specifically. Lastly, FAM76B was found to be expressed in the normal tissues of most human organs, though to different extents. The MAbs produced in this study should provide a useful tool for investigating the biological function(s) of FAM76B.